Book Reviews - Edwards , Peter G.; Piggott , Michael; Thompson , John R. (Archives & Manuscripts, 1977)
Historians and archivists, conferences and books: a review article on World War II: an account of its documents, edited by James E. O’Neill and Robert W. Krauskopf reviewed by Peter G. Edwards; A review in part of Archive-Library relations, edited by Robert L. Clark reviewed by Michael Piggott; Catalogue of manuscripts from the Hayes collection, edited by M. Brenan, M. Ehrhardt and C. Hetherington reviewed by John R. Thompson